A biclausal account of Clitic Left-Dislocations with epithets in Rioplatense Spanish. Issue 1 (24th March 2020) - Estigarribia, Bruno
Abstract : Clitic Left-Dislocations with Epithets in Rioplatense Spanish (CLLD+ep) are sentences with three apparently co-referential direct object constituents: a clitic-left-dislocated topic DP (DP-LD), a clitic (CL) and a post-verbal epithet (DP-ep). Previous studies have proposed that the DP-ep is licensed in-situ as Clitic Doubling and the DP-LD base-generated, or that the DP-ep and the DP-LD are licensed together in a predicative small clause doubled by the clitic. However, data where the DP-LD and the CL are singular but co-occur with a plural DP-ep cast doubt on previous analyses. Here, I explore an analysis of CLLD+ep as an underlyingly biclausal structure subject to deletions. The biclausal structure allows a plural epithet to refer to the plural restrictor set of a syntactically singular quantifier in a previous clause.